UJI BEBERAPA MINYAK ATSIRI SEBAGAI ATRAKTAN LALAT BUAH PADA TANAMAN CABAI MERAH (Capsicum annum L.) - Desita Salbiah; Agus Sutikno; Arianto Rangkuti (Jurnal Agroteknologi, 2013)
Fruit flies is major pest on chilli. Controlling this pest can be used of atractan. The experiment to get species of fruit flies and the most fixed oil type both as atractan fruit flies pest at chilli plant (Capsicum annum L.). The experiment was conducted at Laboratory of Plant Pest and experimental garden University of Riau Pekanbaru, from January until April 2013. The experiment used a Randomized Block Design (RBD) with 4 treatments and 6 replications. The treatments are trap with fixed oil four. Atractan are sweet flag (Acorus calamus), sweet basil (Ocidum minimum), celery (Apium gravoelens) and lemongrass scanted (Andropogon nardus). Results of the research showed catch two fruit flies species. That species are B. dorsalis and B. umbrosa. Sweet basil is best atractan. That can catch fruit flies with averagely 26,83 numbers. All fruit flies which gotten are male fruit flies. Female fruit flies at most gotten of lemongrass scanted with averagely 0,33 number. Fixed oil of sweet basil constitutes at longest atractan its active term with averagely 4,66 days.